Identification of biomarkers related to immune and inflammation in membranous nephropathy: comprehensive bioinformatic analysis and validation - Zhang, Pingna; Geng, Yunling; Tang, Jingyi; Cao, Zijing; Xiang, Xiaojun; Yang, Kezhen; Chen, Hongbo (Frontiers in Immunology, 2023)
Background Membranous nephropathy (MN) is an autoimmune glomerular disease that is predominantly mediated by immune complex deposition and complement activation. The aim of this study was to identify key biomarkers of MN and investigate their association with immune-related mechanisms, inflammatory cytokines, chemokines and chemokine receptors (CCRs). Methods MN cohort microarray expression data were downloaded from the GEO database. Differentially expressed genes (DEGs) in MN were identified, and hub genes were determined using a protein-protein interaction (PPI) network. The relationships between immune-related hub genes, immune cells, CCRs, and inflammatory cytokines were examined using immune infiltration analysis, gene set enrichment analysis (GSEA), and weighted gene co-expression network analysis (WGCNA). Finally, the immune-related hub genes in MN were validated using ELISA. Results In total, 501 DEGs were identified. Enrichment analysis revealed the involvement of immune- and cytokine-related pathways in MN progression. Using WGCNA and immune infiltration analysis, 2 immune-related hub genes (CYBB and CSF1R) were identified. These genes exhibited significant correlations with a wide range of immune cells and were found to participate in B cell/T cell receptor and chemokine signaling pathways. In addition, the expressions of 2 immune-related hub genes were positively correlated with the expression of CCR1, CX3CR1, IL1B, CCL4, TNF, and CCR2. Conclusion Our study identified CSF1 and CYBB as immune-related hub genes that potentially influence the expression of CCRs and pro-inflammatory cytokines (CCR1, CX3CR1, IL1B, CCL4, TNF, and CCR2). CSF1 and CYBB may be potential biomarkers for MN progression, providing a perspective for diagnostic and immunotherapeutic targets of MN.